First Report of the Root-Knot Nematode, Meloidogyne floridensis Infecting Guardian® Peach Rootstock in South Carolina, USA - Reighard Gregory L.; Henderson William G.; Scott Sarah O.; Subbotin Sergei. A. (Journal of Nematology, 2019)
In 2018 to 2019, soil and root samples from some declining peach orchards were collected in Edgefield County, South Carolina, USA. Excavated roots of Guardian® peach (Prunus persica) rootstock showed strong gall symptoms. Extracted root-knot nematodes (RKN) were identified by both morphological and molecular methods as M. floridensis. This is the first detection of the peach RKN in South Carolina and the third state in the USA after Florida and California.